Isolated Cataplexy in the Differential Diagnosis of Drop Attacks: A Case of Successful Clinical Diagnosis and Treatment. (17th July 2012) - Egel, Robert T.; Lee, Anthony; Bump, Thomas; Javois, Alexander
Abstract : Drop attacks are sudden spontaneous falls that are not accompanied by alteration of consciousness and are followed by immediate recovery. Cataplexy, which is usually associated with narcolepsy, is one of the causes of drop attacks. We report a patient with the rare condition of cataplexy without associated narcolepsy (isolated cataplexy). Isolated cataplexy should be included in the differential diagnosis when a patient presents with recurrent drop attacks and normal diagnostic test results.